2019
DOI: 10.1108/jeim-05-2019-0136
|View full text |Cite
|
Sign up to set email alerts
|

What drives customer satisfaction and word of mouth in mobile commerce services? A UTAUT2-based analytical approach

Abstract: Purpose The purpose of this paper, which is based on the UTAUT2 model, is to develop and evaluate a predictive model of customer satisfaction related to mobile commerce (m-commerce) and the willingness to recommend this service to others. Design/methodology/approach The study was conducted based on a sample of 402 respondents. Confirmative factor analysis was used to evaluate the validity of the model, while structural equation modeling (SEM) was used to test the hypotheses. Finally, artificial neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 79 publications
11
68
1
10
Order By: Relevance
“…Nonetheless, research has questioned the linearity of relationships in the models of technology adoption (Rondan-Cataluña et al, 2015 ). However, the most recent works that have applied non-linearity to technology acceptance models have used the Artificial Neural Networks (ANN) analysis tool (Sharma et al, 2016 ; Ooi et al, 2018 ; Chavoshi and Hamidi, 2019 ; Kalinić et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, research has questioned the linearity of relationships in the models of technology adoption (Rondan-Cataluña et al, 2015 ). However, the most recent works that have applied non-linearity to technology acceptance models have used the Artificial Neural Networks (ANN) analysis tool (Sharma et al, 2016 ; Ooi et al, 2018 ; Chavoshi and Hamidi, 2019 ; Kalinić et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the residents are satis ed with PPAPs, meaning that they are satis ed with the services provided by the State Grid, then they will rely on State Grid and continue to participate in PPAPs. The predecessors also found a signi cant role between trust and customers' satisfaction [32,57]. Inadequate power supply and unreliable power service will lead to end-users' dissatisfaction with power service [60].…”
Section: Discussionmentioning
confidence: 99%
“…This study de nes satisfaction as the sense of happiness formed by the bene ciaries through the previous expectation and actual perception. Some scholars con rmed a close connection between trust and users' satisfaction in mobile commerce [32,58]. In addition, scholars found that consumers' green satisfaction has a signi cant effect on green trust in the research on users' word-of-mouth intentions of the green hotel industry [43].…”
Section: Bene Ciaries' Satisfactionmentioning
confidence: 99%
“…Its precedents lie in perceived usefulness, extrinsic motivation and fit in the job. In addition to the original study (Venkatesh et al, 2003 ), this construct has been used extensively in later research (Chauhan and Jaiswal, 2016 ; Lakhal, 2017 ; Cabrera-Sánchez and Villarejo-Ramos, 2019 ; Kalinić et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%